Pengadaan Barang dan Jasa Pemerintah - Yusri, Yusri (Media Ilmiah Teknik Sipil, 2017)
Procurement of goods and services is needed. Mechanism for the implementation of Procurement of Goods / Services, namely through self-management and / or selection of goods / services providers. Self-management is a work that is planned, done and supervised by the institution itself, where in its implementation it can be carried out by PPK, other government agencies or community groups / NGO grant recipients, while for the selection of providers of goods / services can be through: public auctions, simple auctions, direct appointments , contests / contests, direct elections, limited auctions, direct procurement. Principles in the procurement of government goods / services include principles of efficiency, effective principles, principles of transparency, open principles, competing principles, principles of fairness / non-discrimination and principles of accountability. While ethics that must be obeyed include carrying out duties in an orderly manner, full of sense of responsibility, for the smooth and accurate achievement of the objectives of procuring goods / services, working professionally by upholding honesty, independence, and keeping information confidential, not directly influencing or indirect results resulting in unfair competition, a decrease in the quality of the procurement process. Responsible for all decisions determined in accordance with their authority, preventing the occurrence of conflict of interest of parties involved directly or indirectly in the procurement process. Prevent financial leaks and losses. In the implementation of procurement of goods and services, it should not blame authority and carry out joint activities with the aim of personal gain, class, or other parties directly or indirectly, not accepting, offering and or promising to give gifts, rewards, or anything to anyone what is known or deserves to be suspected related to the procurement of goods / services.